Common co-morbid conditions associated with type 2 diabetes mellitus - Shaha, Kartick Chanda; Rahman, Md Shamsur; Shahnaz, Tasmin; Habibunnahar, - (Bangladesh Journal of Medical Science, 2020)
Objective: The aim of the present study was to find out the common co-morbid conditions associated with type 2 diabetes mellitus. Methods: A descriptive, cross sectional study was conducted from January 2016 to June 2016 among 300 patients attending at Medicine outpatient department of the Community Based Medical College Hospital and Endocrine outpatient department of the Mymensingh Medical College Hospital after obtaining requisite consent from the patients. Data were collected through the interviewing of the patients. The collected data were entered into the computer and analyzed by using SPSS (version 20.1) to know the common co-morbid conditions associated with type 2 diabetes mellitus. The study was approved by the institutional ethical committee. Results: In a pool of 300 type 2 diabetics, Most of the patients (57.3%) belonged to the middle age group 41-60 years. More than half of the respondents were female (n=223, 74.3%). Among 300 cases, 188 patients had shown association with different co-morbid conditions. Female patients (77%) suffered from more co-morbid conditions than male patients (23%). Hypertension was the most commonly associated disease (65.42%) with DM. Conclusion: Most of the diabetic patients have co-morbid conditions. Hypertension was the most commonly associated disease with DM. Bangladesh Journal of Medical Science Vol.19(2) 2020 p.237-239